Surgical treatment of temporal lobe epilepsy: comparative results of selective amygdalohippocampectomy versus anterior temporal lobectomy from a referral center in Brazil - Almeida, Laryssa Crystinne Azevedo; Lobato, Vanessa Alves; Santos, Maria do Carmo Vasconcelos; Moraes, Aline Curcio de; Costa, Bruno Silva (Arquivos de Neuro-Psiquiatria, 2023)
Background Temporal lobe epilepsy (TLE) is a high prevalence neurological disorder. Surgery has emerged as a promising treatment.Objective The objective of this work is to compare the surgical results of anterior temporal lobectomy (ATL) versus selective amygdalohippocampectomy (SAH) in a cohort of 132 patients.Methods We performed a retrospective study of 146 patients operated for TLE from 2008 to 2019. Initially, 13 patients were excluded from the study due to insufficient medical record data or follow-up loss. One patient was excluded from the analysis of the results due to death in the first postoperative week. We used the ILAE scale to classify seizure control after surgery. In patients with left hippocampal sclerosis, SAH was performed and in right temporal lobe epilepsy, ATL was the approach of choice.Results The mean follow-up time after surgery was 57.2 months (12–137). In our data analysis, we found that the group of patients undergoing ATL had a higher prevalence of being completely seizure-free (ILAE I) (57.1% versus 31%) and a higher rate of satisfactory seizure control (88.6% versus 69.3%) p = 0,006, when compared with patients undergoing SAH.Conclusion The literature is still controversial about seizure control concerning the technique used due to the lack of a robust methodology. Our data analysis identified the superiority of ATL over SAH in seizure outcomes. ATL may be the best option for adequately controlling seizures with minimal additional morbidity in countries with a cost limitation for extended propaedeutics.
Keywords: Epilepsy, Temporal Lobe; Hippocampal Sclerosis; Anterior Temporal Lobectomy; Epilepsies, Partial